2021
DOI: 10.20956/icon.v5i2.10859
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Phlebitis Following the Use of Peripheral IV Line at X Hospital

Abstract: Introduction: Intravenous (IV) line infusion therapy is a therapy given to patients who are admitted or having a specific therapy. The IV-line therapy may include fluid therapy, medication administration and blood therapy. Based on the data found in Hospital X, there were 30 incidence of phlebitis in 2017. This study aimed to describe the factors of phlebitis incidence in X hospital. Method: This study was a retrospective study using 50 clinical record of the inpatient patients. The inclusion criteria were all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In this present study, 62.3 % of phlebitis has occurred in males and 37.7 % in females but no significant association was found between gender and phlebitis. The findings of the present study were in accordance with the study finding of Jacinto et al (2014) 5 which showed no association between gender and phlebitis, these findings are also in line with the findings of Tefera et al (2020) 1 which showed no association between gender and phlebitis but the findings of the present study were in contrast with the study findings of Sijabat M et al ( 2021) 12 which showed that male gender is a risk factor for phlebitis and the study done by Luyu et al(2020) 15 in which author found an association between gender and phlebitis.…”
Section: Discussionsupporting
confidence: 90%
“…In this present study, 62.3 % of phlebitis has occurred in males and 37.7 % in females but no significant association was found between gender and phlebitis. The findings of the present study were in accordance with the study finding of Jacinto et al (2014) 5 which showed no association between gender and phlebitis, these findings are also in line with the findings of Tefera et al (2020) 1 which showed no association between gender and phlebitis but the findings of the present study were in contrast with the study findings of Sijabat M et al ( 2021) 12 which showed that male gender is a risk factor for phlebitis and the study done by Luyu et al(2020) 15 in which author found an association between gender and phlebitis.…”
Section: Discussionsupporting
confidence: 90%
“…As many as 84% of respondents who received continuous insulin therapy felt pain at the infusion site (Taleb et al, 2018). Incorrect location of the infusion order can also cause pain, a phlebitis symptom (Sijabat et al, 2021). In this study, respondents did not feel pain because of the relatively short order time, normal saline infusion fluids, small intravenous catheters, and the selection of the correct location.…”
Section: Discussionmentioning
confidence: 60%
“…The evidence revealed that when drugs or blood is administer, the vein become in ltrated faster due to the irritation effect of drug and clotting and reaction of blood on the blood vessels (42,43). The irritation effects and reaction of blood make the blood vessels be in amed.…”
Section: Discussionmentioning
confidence: 99%